Komórki macierzyste – nowe perspektywy w leczeniu chorób siatkówki - Machalińska, Anna; Karczewicz, Danuta; Machaliński, Bogusław (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The progress of clinical science since a few last years indicates the possibility that stem cells could be used in the treatment of retinal disorders. The bone marrow seems to be the most available source of the stem cells for such purposes. This review describes the latest attempts to use the stem cells, isolated from the bone marrow, in the treatment of retinal injuries. The research performed in animal models, so far gives hope to use that innovatory strategy in humans.